Do genetic variations in proximal tubule transporters influence tenofovir-induced renal dysfunction? An exploratory study in a Ghanaian population. (14th February 2020) - Neary, M; Olagunju, A; Sarfo, F; Phillips, R; Moss, D; Owen, A; Chadwick, D
Abstract: Objectives: To assess associations between polymorphisms within genes encoding proximal tubule transporters implicated in tenofovir renal clearance and kidney tubular dysfunction (KTD), chronic kidney disease (CKD) and individual biochemical parameters. Patients and methods: The study included a cohort of HIV-positive Ghanaians receiving regimens containing tenofovir disoproxil fumarate ( n  = 66) for at least 6 months prior to study enrolment. SNPs in ABCC10, ABCC2 and ABCC4 were selected for analysis based on previous published associations. All SNPs were genotyped by real-time PCR allelic discrimination. Creatinine clearance (CLCR ), serum and urine creatinine concentrations and biochemical measures of KTD were assessed. Statistical significance was determined through univariate linear or binary logistical regression ( P  ≤ 0.05). Results: None of the SNPs evaluated was associated with CKD or KTD. A trend between body weight and higher incidence of CKD ( P  = 0.012, OR = 0.9) was observed. ABCC10 2843T>C (rs2125739) was significantly associated with lower log10 baseline creatinine ( P  = 0.001, β= −0.4), higher baseline CLCR ( P  = 0.008, β = 65.2) and lower CLCR after 1 year ( P  = 0.024, β= −26.6). Conclusions: This study demonstrates an association of ABCC10 rs2125739 with indicators of declining renal function and builds on current knowledge of this interaction within a Ghanaian cohort.